Regularização fundiária sustentável como instrumento para o direito à cidade: por uma nova ética urbana à luz de Ronald Dworkin - ALVES, Maria Júlia Almeida da Silva (Universidade Federal do Pará, 2015)
This work make an analyses of the urbanization’s process, which principal characteristic is the economic social and spatial segregation of low-income population, noticeable by the phenomenon of urban periphery experienced by this segment of society. Without ways to formal access to urban land, the low-income population residing in urban areas promotes the illegal occupation of areas that lack or poor infrastructure and urban services, which generally are not required by the formal housing market. The unequal form of urban spaces appropriation is because of the capitalist way of appropriation. In this context of unequality, exclusion, segregation it is insert the issue of illegal occupation of the margins of water courses located in urban areas, which are especially protected by environmental legislation, what lead us to the principal target of this work: the possibility of implementing actions of sustainable land regularization in occupations of social interest, consolidated in urban areas located on the banks of water courses, analyzed as a tool to combat the social-spatial segregation process experienced by the low-income population due to the capitalist production process of urban spaces. To do so since the concrete analyses of two cases it uses the regularization actions as an instrument for achieving the right to sustainable cities, housed in the Brazilian legal in Federal Law No. 10.257/2001, claiming it as a fundamental right, based on equality theory of legal philosopher Ronald Dworkin. The problematic issue that the work reveals is the apparent conflict between the need for care of the fundamental rights of the resident population of these occupations and the duty to maintain an ecologically balanced environment, of which solution is guided by weighing up the principles and values instilled in them, based on the concept of law as integrity, also developed by Ronald Dworkin.